Peningkatan Kualitas Produksi Keripik Umbi-Umbian Menggunakan Alat Pengering Buatan - Muhammad Firmansyah; Arfida Boedirochminarni (Program Studi Ekonomi Pembangunan, 2025)
This community service activity aims to provide solutions for partners who have problems and experience difficulties in drying tuber chips during cloudy/rainy weather. The activity implementation team designed a dryer (spinner) to help the drying process despite insufficient sunlight. Using a dryer (spinner) has been proven to increase the productivity of tuber chips by around 200% during cloudy or rainy weather compared to drying without a spinner. This dryer (spinner) uses low-power electricity (300 watts). It is designed with fairly simple technology so that partners can easily operate it and use it in subsequent community service activities.